Effects of climate change on yak production at high altitude - KRISHNAN, G; PAUL, V; HANAH, S S; BAM, J; DAS, P J (The Indian Journal of Animal Sciences, 2016)
Yak is considered the life-line of highland pastoral nomads who raise them on high altitude ranges under transhumance. Yak production at high-altitude alpine ranges may be affected due to the gradual increase of environmental temperature as a result of impending climate change. The mean environmental temperature of yak habitat at 3,000 m above mean sea level in Northeastern Indian Himalaya, varying from 1.2 to 11.1°C and 7.9 to19.7°C during winter and summer seasons, respectively, evidencing the heat stress to the yaks in summer with THI more than 52. When environmental temperature exceeds 13°C, adaptive mechanisms of body accelerate respiration rate and heart rate to cope with heat stress in yaks. It was reported that the climate change is already witnessed at high altitude with average rise of environmental temperature 0.01 to 0.04°C/year and the expected increase of 2– 3°C have potentially catastrophic for high-altitude animals and ecosystem. The alpine pasture decreased in vegetative above ground biomass and composition which results in starvation or loss of body condition appeared to be manifested as reduced fertility in yak with low milk yield. Further, climate change may result in increase of pests and diseases at the lower permanent settlements of sub-alpine region thereby making these areas incompatible for yaks. Mitigation of heat stress in yak possibly can be done through three means by physical modification of the environment, improved nutritional management and genetic development of strains that would be less sensitive to heat stress.